3D mechanics of scaled membranes. (1st April 2022) - Shafiei, Ali; Barthelat, Francois
Abstract: Scale-covered skins are excellent examples of natural flexible protective systems. With segmented hard scales bonded or embedded onto a deformable skin, these natural structures provide useful combinations of puncture resistance and flexural compliance. The interaction of the scales with the substrate and the scales themselves is the key to such high-performance systems. In this work we investigate the 3D mechanics of puncture and flexion for a range of designs for scale-covered systems, using validated discrete element models (DEM) of the scales. The scales are orders of magnitude harder and stiffer than the substrate, so that they can be considered rigid for the purpose of mechanical modeling. Our main findings are that scales with no slant angles positioned in arrays increase puncture resistance compared to isolated scales, but only by way of interactions through the substrate and with much less extent by direct contact between scale. Direct scale-scale interaction can however be much improved by slanting the scales which we also examined in this work. We also examined the in-plane kinematics of scales, and identified interlocking mechanisms between rows of scales that further increase toughness. Dart- and hexagon-shape scales combined all these mechanisms in the most effective way among the designs we explored here. This study provides new insights into the effect of the base shape and the slant angle of the scales on the mechanical behavior of scale-covered systems, which in turn can help in the design and optimization of improved protective systems.